Selection of wheat genotypes for biomass allocation to improve drought tolerance and carbon sequestration into soils. (18th February 2019) - Mathew, Isack; Shimelis, Hussein; Mutema, Macdex; Clulow, Alistair; Zengeni, Rebecca; Mbava, Nozibusiso; Chaplot, Vincent
Abstract: The biomass allocation pattern of plants to shoots and roots is a key in the cycle of elements such as carbon, water and nutrients with, for instance, the greatest allocations to roots fostering the transfer of atmospheric carbon to soils through photosynthesis. Several studies have investigated the root to shoot ratio (R:S) biomass of existing crops but variation within a crop species constitutes an important information gap for selecting genotypes aiming for increasing soil carbon stocks for climate change mitigation and food security. The objectives of this study were to evaluate agronomic performance and quantify biomass production and allocation between roots and shoots, in response to different soil water levels to select promising genotypes for breeding. Field and greenhouse experiments were carried out using 100 genotypes including wheat and Triticale under drought‐stressed and non‐stressed conditions. The experiments were set‐up using a 10 × 10 alpha lattice design with two replications under water stress and non‐stress conditions. The following phenotypic traits were collected: number of days to heading (DTH), number of productive tillers per plant (NPT), plant height (PH), days to maturity (DTM), spike length (SL), kernels per spike (KPS), thousand kernel weight (TKW), root biomass (RB), shoot biomass (SB), root to shoot ratio (R:S) and grain yield (GY). There was significant ( p  < 0.05) variation for grain yield and biomass production because of genotypic variation. The highest grain yield of 247.3 g/m 2 was recorded in the genotype LM52 and the least was in genotype Sossognon with 30 g/m 2 . Shoot biomass ranged from 830 g/m 2 (genotype Arenza) to 437 g/m 2 (LM57), whilst root biomass ranged between 603 g/m 2 for Triticale and 140 g/m 2 for LM15 across testing sites and water regimes. Triticale also recorded the highest R:S of 1.2, whilst the least was 0.30 for wheat genotype LM18. Overall, drought stress reduced total biomass production by 35% and R:S by 14%. Genotypic variation existed for all measured traits useful for improving drought tolerance, whilst the calculated R:S values can improve accuracy in estimating C sequestration potential of wheat. Wheat genotypes LM26, LM47, BW140, LM70, LM48, BW152, LM75, BW162, LM71 and BW141 were selected for further development based on their high total biomass production, grain yield potential and genetic diversity under drought stress.